2019
DOI: 10.1186/s13643-019-0993-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and effectiveness of young people-specific, integrated out-of-hospital services: a protocol for a systematic review

Abstract: Background The need for specific services for young people is being widely recognized to address their unique and complex health needs. Growing evidence in integrated health services shows promise in improving the efficiency of health systems. Although there is a broad agreement on the need for integrated care in young people, there has been no systematic effort to evaluate the provision of integrated out-of-hospital health services for this group. The proposed systematic review aims to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…The main study finding that IC hospitals were more efficient than non-IC hospitals is congruent with previous research in the literature [25][26][27][28][29]. However, our study is at variance with literature that reported negative effects of integration on efficiency [30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main study finding that IC hospitals were more efficient than non-IC hospitals is congruent with previous research in the literature [25][26][27][28][29]. However, our study is at variance with literature that reported negative effects of integration on efficiency [30].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it remains unclear from that literature the direction of effect, if any, of IC on hospital efficiency. Some studies demonstrated that integrated partnerships and a coordinated continuum of services dedicated to the treatment of specialized diseases or a defined population may improve hospital efficiency [25][26][27][28][29]. However, weak and, on occasions, negative impacts of IC on hospital efficiency were also found [30,31].…”
mentioning
confidence: 99%
“…[54] The main study nding that IC hospitals were more e cient than non-IC hospitals is congruent with previous research in the literature. [25][26][27][28][29] However, our study is at variance with literature that reported negative effects of integration on e ciency. [30] This discrepancy could be explained by differences in the unit of analysis and the way integration was measured in previous studies.…”
Section: Discussioncontrasting
confidence: 90%
“…Some studies demonstrated that integrated partnerships and a coordinated continuum of services dedicated to the treatment of specialized diseases or a de ned population may improve hospital e ciency. [25][26][27][28][29] However, weak and, on occasions, negative impacts of IC on hospital e ciency were also found. [30][31] As such, there is an opportunity to add to the literature by directly assessing the impact of IC on hospital e ciency.…”
mentioning
confidence: 99%